How Language Supports Adaptive Teaching Through a Responsive Learning Culture. Issue 3 (2nd July 2016) - Johnston, Peter; Dozier, Cheryl; Smit, Julie
Abstract : For students to learn optimally, teachers must design classrooms that are responsive to the full range of student development. The teacher must be adaptive, but so must each student and the learning culture itself. In other words, adaptive teaching means constructing a responsive learning culture that accommodates and even capitalizes on diversity to ensure that each student is learning optimally. There are 2 primary resources for accomplishing this, engagement and the classroom talk that the teacher orchestrates.